Intravenous iron for treatment of iron deficiency anemia during pregnancy and associated maternal outcomes. (31st December 2023) - Burn, Martina S.; Lundsberg, Lisbet S.; Culhane, Jennifer F.; Partridge, Caitlin; Son, Moeun
Abstract: Background: More than 40% of pregnant patients worldwide are anemic, with at least half resulting from iron deficiency anemia (IDA). Anemia in pregnancy is linked with adverse maternal and neonatal outcomes. Treatment for IDA is iron supplementation; however, the optimal route of administration remains unclear. We sought to investigate whether patients with IDA who received intravenous iron (IVI) had decreased odds of maternal morbidity compared to patients who did not. Methods: This is a retrospective cohort study of pregnant patients with presumed IDA with term deliveries at a tertiary hospital from 2013–2021. Data were extracted from the hospital's electronic medical record using standardized definitions and billing codes. Patients who received antepartum IVI were compared to patients who did not. The primary outcome was a maternal morbidity composite inclusive of receipt of blood transfusion, hysterectomy, admission to the intensive care unit or death. Bivariate analyses and multivariable logistic regression modelling were performed adjusting for potential confounders. Results: Of 45, 345 pregnancies, 5054 (11.1%) met eligibility criteria. Of these, 944 (18.7%) patients received IVI while 4110 (81.3%) did not. Patients who received IVI had higher risk baseline characteristics. They experienced a greater increase in hematocrit from pregnancy nadir to delivery admission (4.5% vs. 3.3%, p  < .01). Despite this, patients who received IVI had higher odds of the maternal morbidity composite (OR 1.47, 95%CI 1.11–1.95). This finding persisted after adjusting for potential confounders, although the strength of the association became attenuated (aOR 1.37, 95%CI 1.02–1.85). Odds of the morbidity composite were not elevated among patients who received a full IVI treatment course (OR 1.2, 95% CI 0.83–1.90). Discussion: Odds of the maternal morbidity composite were increased among patients who received IVI despite greater increases in hematocrit. The effect was attenuated after adjusting for potential confounders and was not significant among patients who completed a full treatment course.